PENGARUH HAMBATAN SAMPING TERHADAP VOLUME LALU LINTAS DENGAN MENGGUNAKAN REGRESI LINIER BERGANDA (Studi Kasus: Ruas Jalan Ryacudu Kota Bandar Lampung) - Chandra Alip Pratama; Andantino Putra Palsamu; Estu Emma Apriliana (Kampus Akademik Publiser, 2026)
Lampung is the southernmost province on the island of Sumatra and serves as the gateway to land and sea transportation from Sumatra to Java. Its provincial capital, Bandar Lampung, as the center of the city is not free from congestion problems. Ryacudu Road is one of the densest roads in Bandar Lampung City, particularly in the Sukarame sub-district connecting the Way Halim Fly Over and the Ryacudu Canal Road. Points of congestion occur along this road, namely illegal parking on the right and left sides of the road caused by side friction. As side friction increases, this study aims to examine how much side friction influences the traffic volume on Ryacudu Road, under the title